Visualization of combustion characteristic of diesel in premixed methanol–air mixture atmosphere of different ambient temperature in a constant volume chamber. (15th June 2016) - Yin, Zenghui; Yao, Chunde; Geng, Peilin; Hu, Jiangtao
Highlights: The combustion characteristic of diesel in MAA and AA was investigated. MAA has longer ignition delay and FLoL compared with AA at lower temperature. Diesel combustion in MAA is more sensitive to temperature variation. The inhibitory effect of methanol weakens with increasing ambient temperature. Abstract: Methanol has drawn increasing attention in recent years as an alternative fuel due to its potential to reduce NOX and soot emissions. In this work, the combustion characteristic of diesel in air atmosphere (AA) and premixed methanol–air mixture atmosphere (MAA) were studied in an optical constant volume chamber under different in-cylinder temperature, ranging from 840 to 960 K. Time resolved images and natural flame luminosity were captured by a high speed camera, and flame lift-off lengths (FLoL) were acquired. It is found that MAA has longer ignition delay and lift-off length compared with AA at lower temperature until 920 K, and is more sensitive to temperature variation. With the increase of ambient temperature, the ignition delay and FLoL of diesel for both atmospheres become shorter, and the difference between the two atmospheres due to methanol's inhibitory effect gets smaller, and becomes almost negligible at 960 K. Comparison of natural flame luminosity gives the same trend. The ambient temperature is shown to be critical to the combustion characteristics of diesel in MAA, which has an important effect on the chemical kinetics between methanol and diesel due to temperature sensitiveness of the conversion reaction of OH and H2 O2 .